The philosophy of grammar - Jespersen, Otto (G. Allen & Unwin, 1988)
London 1924 1st Allen & Unwin. 8vo., 859pp., index, hardcover. Near Good, inner hinges cracked, lower corners bumped, spine ends a bit frayed.